Clustering entrepreneurial and ınnovative universities in turkey according to their relevance to ındustry 4.0 - Türkay DERELİ; ÖZGE VAR; Alptekin Durmusoglu (My University, 2020)
Industry 4.0 differentiates production and business models through connecting embedded system, production technologies, and smart production processes. Preparing the young generation to this change is a challenge for higher education. In this study, the adaptation of the entrepreneurial and innovative universities in Turkey to Industry 4.0 is linked with their relevance level to Industry 4.0. To represent the relevance level of universities, a cluster analysis is put forward. Three criteria, named as the number of academic publications related to Industry 4.0, the number of physical structures that facilitate the adaptation to Industry 4.0, and the number of events organized by the universities within the Industry 4.0 concept, were selected for the clustering analysis. To access the number of academic publications of universities, ISI Web of Science database was used. “Industry 4.0” and its components were used as keywords. Both the websites of the each university and Google search results were used to access the values of remaining two criteria. The obtained data were used for K-means clustering analysis. The optimal number of cluster was determined as five with the elbow method. It is thought that the results of the study could be used as an indicator for universities to determine their Industry 4.0 road maps.Keywords: Industry 4.0, Elbow method, K-means algorithm.